Influence of organisational culture on the implementation of health sector reforms in low- and middle-income countries: a qualitative interpretive review - Rahab Mbau; Lucy Gilson (Taylor & Francis Group, 2018)
Background: Health systems, particularly in low- and middle-income countries, are commonly plagued by poor access, poor performance, inefficient use and inequitable distribution of resources. To improve health system efficiency, equity and effectiveness, the World Development Report of 1993 proposed a first wave of health sector reforms, which has been followed by further waves. Various authors, however, suggest that the early reforms did not lead to the anticipated improvements. They offer, as one plausible explanation for this gap, the limited consideration given to the influence over implementation of the software aspects of the health system, such as organisational culture - which has not previously been fully investigated. Objective: To identify, interpret and synthesise existing literature for evidence on organisational culture and how it influences implementation of health sector reforms in low- and middle-income countries. Methods: We conducted a systematic search of eight databases: PubMed; Africa-Wide Information, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Econlit, PsycINFO, SocINDEX with full text, Emerald and Scopus. Eight papers were identified. We analysed and synthesised these papers using thematic synthesis. Results: This review indicates the potential influence of dimensions of organisational culture such as power distance, uncertainty avoidance, and in-group and institutional collectivism over the implementation of health sector reforms. This influence is mediated through organisational practices such as communication and feedback, management styles, commitment and participation in decision-making. Conclusion: This interpretive review highlights the dearth of empirical literature around organisational culture and therefore its findings can only be tentative. There is a need for health policymakers and health system researchers to conduct further analysis of organisational culture and change within the health system.